2005
DOI: 10.1037/0033-3204.42.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Client Attachment to Therapist, Depth of In-Session Exploration, and Object Relations in Brief Psychotherapy.

Abstract: Two studies explored attachment in psychotherapy. In the 1st study, clients (N ϭ 38) in time-limited therapy completed the Experiences in Close Relationships Scale as a measure of adult attachment, the Client Attachment to Therapist Scale (CATS), Working Alliance Inventory (WAI), and measures of session depth and smoothness. Consistent with J. Bowlby's (1988) concept of a secure base promoting greater exploration, secure attachment to therapist was significantly associated with greater session depth and smoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
123
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(144 citation statements)
references
References 47 publications
14
123
0
7
Order By: Relevance
“…Researchers and theoreticians have suggested that the therapist-patient relationship may also be conceptualized and understood using Attachment Theory concepts (e.g. Daniel, 2006;Mallinckrodt, Porter, & Kivlighan, 2005;Obegi & Berant, 2009). According to Mallinckrodt (2010), the therapeutic relationship meets the criteria that define an attachment relationship.…”
Section: The Therapist-patient Relationship As An Attachment Relationmentioning
confidence: 99%
“…Researchers and theoreticians have suggested that the therapist-patient relationship may also be conceptualized and understood using Attachment Theory concepts (e.g. Daniel, 2006;Mallinckrodt, Porter, & Kivlighan, 2005;Obegi & Berant, 2009). According to Mallinckrodt (2010), the therapeutic relationship meets the criteria that define an attachment relationship.…”
Section: The Therapist-patient Relationship As An Attachment Relationmentioning
confidence: 99%
“…Securely attached adults are more able to trust and to be kind, sensitive, empathetic, compassionate, and open (Collins & Read, 1990;Kunce & Shaver, 1994;Lopez & Brennan, 2000;Mallinckrodt, Porter, & Kivlighan, 2005;Mikulincer, 1997;Mikulincer & Orbach, 1995;Rogers, 1961) than those with high levels of attachment anxiety or avoidance. They show love and forgiveness, feel connected, commit to altruistic and ethical behavior, and have a generally positive view of others (Lopez & Brennan, 2000;Mikulincer & Shaver, 2003, 2007aMikulincer, Shaver, Gillath, & Nitzberg, 2005).…”
mentioning
confidence: 99%
“…Este fenómeno de causalidade recíproca tem levado a que este instrumento tenha sido utilizado em numerosas investigações recentes (e.g., Jerome & Liss, 2005;Mallinckrodt, Porter, & Kivlighan, 2005;Obegi, Morrison, & Shaver, 2004) e traduzido em diversas línguas (e.g., Hebraico, por Mikulincer & Florian, 2000;Francês, por Lafontaine & Lussier, 2003;Chinês, por Mallinckrodt & Wang, 2004). Todas estas razões justificavam amplamente a sua tradução e validação numa versão Portuguesa.…”
unclassified